Internal Shariah Audit Effectiveness And Its Determinants: Case Of Islamic Financial Institutions In Malaysia - Nurazalia Zakaria; Noraini Mohd Ariffin; Nor Hafizah Zainal Abidin (Center For Islamic Area Studies Kyoto University, 2024)
Volume :12